1997
DOI: 10.1068/p260905
|View full text |Cite
|
Sign up to set email alerts
|

Visual Perception of Motor Anticipation in Cursive Handwriting: Influence of Spatial and Movement Information on the Prediction of Forthcoming Letters

Abstract: The execution of a graphemic sequence is constrained by spatial demands that result in fluctuations of letter shape and movement time. When producing two letters (ll, le, or ln) the movement time and the letter shape of the first letter depend on the execution constraints of the second one. The motor system thus anticipates the production of the forthcoming graphemic sequence during the production of the first letter. An experiment is reported the aim of which was to examine whether the visual system could exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 18 publications
2
57
0
1
Order By: Relevance
“…For the uppercase letters of the alphabet with curved traces, such as C, S, R, or O, we conducted a previous stroke segmentation analysis based on the tangential velocity minima in the velocity profile (see Figure 2). This criterion for stroke segmentation is classical in studies of motor control and has been used in many studies in handwriting (see Orliaguet, Kandel, & Boë, 1997, for an example). As Figure 2 shows, an S, for instance, has three strokes.…”
Section: Methodsmentioning
confidence: 99%
“…For the uppercase letters of the alphabet with curved traces, such as C, S, R, or O, we conducted a previous stroke segmentation analysis based on the tangential velocity minima in the velocity profile (see Figure 2). This criterion for stroke segmentation is classical in studies of motor control and has been used in many studies in handwriting (see Orliaguet, Kandel, & Boë, 1997, for an example). As Figure 2 shows, an S, for instance, has three strokes.…”
Section: Methodsmentioning
confidence: 99%
“…If an actor pretends, say, that a suitcase he is carrying is heavier than it actually is, his movements will have a non-natural kinematics that can be detected by observers. Another series of experiments (Orliaguet et al, 1997;Kandel et al, 2000) investigated motor anticipation in the perception of handwriting gestures. For instance, when writing an l, the kinematics of the graphic production is influenced by anticipation of the next letter to be written and will differ according to whether the l is to be followed by another l, an i or a n. It was shown that the visual system can exploit these differences to predict the second letter.…”
Section: Imagining and Observing Actions: Simulation And The Limits Omentioning
confidence: 99%
“…Clearly, some of the contextual variations affecting the ongoing action provide clues on what the forthcoming action will be. It has been shown (Kandel, Orliaguet, & Boe, 1994;Orliaguet, Kandel, & Boe, 1997) that, by viewing only a dynamic display of the letter I while it is being written, observers can reliably predict the identity ofthe following letter well before transition cues become available. This specific form of perceptual anticipation was demonstrated both with isolated digrams and with digrams embedded within words, irrespective ofwriting size or mean velocity (Kandel, Boe, & Orliaguet, 1993;Kandel, Orliaguet, & Boe, 1995).…”
mentioning
confidence: 99%
“…Our first aim was to show that the relevant cues in this case are kinematic. Although coarticulation may manifest itself in subtle context-dependent variations of the shape of the movement (Orliaguet et al, 1997), we wanted to demonstrate that anticipation is not trivially based on the ability to discriminate these geometrical factors. Thus, the geometrical features of the dynamic stimuli were kept invariant across conditions.…”
mentioning
confidence: 99%